Administrative Leadership and Quality Assurance Practices in Private Higher Education Institutions in the Philippines: A Case of Northeastern College - Bautista, Tomas (International Journal of Arts, Sciences and Education, 2026)
Quality assurance and effective administrative leadership are essential in sustaining institutional effectiveness and academic excellence in higher education institutions. This study explored the administrative leadership experiences and quality assurance practices in Northeastern College, Santiago City. Using a qualitative phenomenological research design, data were gathered from purposively selected administrators, deans, program heads, and quality assurance personnel through semi-structured interviews. Thematic analysis revealed that collaborative leadership, participatory governance, strategic planning, and continuous quality improvement significantly strengthened institutional management and accreditation practices. Participants emphasized that leadership support, faculty engagement, and organizational adaptability contributed to effective quality assurance implementation. However, challenges related to workload pressures, documentation requirements, communication barriers, and resource limitations affected governance processes. The findings highlight the importance of transformational leadership and collaborative quality assurance mechanisms in promoting institutional sustainability and educational excellence in private higher education institutions.